DEPENDENCE OF SEASONAL BROODING DYNAMICS OF THE BEES ON THE SPECIES COMPOSITION OF NECTARIFEROUS PLANTS - M. A. Abakarova (Юг России: экология, развитие)
Aim. The aim of the study is to reveal the relationship between the collection of pollen, nectar and seasonal brooding dynamics of the bees of the gray mountain Caucasian family; to study their behavior when changing the floristic composition, and also the honey production of honey plants.Methods. Using the frame-grid method, we succeeded to calculate the number of eggs laid by the queen bee. Also, the study allowed comparing the collection of nectar and pollen from each species of honey plants; the species composition of plants and honey content were studied as well.Results. We identified the number of bees that bring pollen and nectar to the hive. The activity of pollen gatherers is associated with the pulse of the queen bee to lay eggs and a large number of sealed brood in the hives. Were also determined the duration of flowering, the potential of honey-yielding plants and the dynamics of the collection of nectar and pollen for the season of 2013.Conclusion. The findings obtained make it possible to present a more specific picture of species diversity, honey production, ecology and the distribution of the melliferous resources of the studied area. The analysis of the obtained findings allows concluding that the daily dynamics of pollen gatherers increases in the spring period by May and June, and the queen bee lays eggs more effectively during this period.